Alternative classification framework for engineering capability enhancement - Patamakajonpong,M. (Emerald Group Publishing Ltd., 2015)
© 2015, Emerald Group Publishing Limited. Purpose: This paper aims to present an alternative practical framework to classify the skill and knowledge of the individual trainees by comparing it with the expert in an organization. This framework gives the benefit to the organization in order to know the ability level of the personnel and to be able to provide the personnel development method both in academic learning and workplace learning. Design/methodology/approach: This research develops the framework based on relevant methodologies. Competency-Based Development is applied to investigate the knowledge and skill of the specific task. Knowledge Engineering is used to capture the experiences and construct knowledge model from relevance parties. Capability Maturity Model is then adapted to develop the capability and maturity level of the personnel. It can then be used to cluster the knowledge and skill. Finally, the Substation Maintenance Department of Provincial Electricity Authority (PEA), Thailand, is selected as a case study to test the proposed framework. Findings: The results have shown that the proposed framework can be utilized to identify the capability level of the individual personnel. Furthermore, the appropriate maturity development of the employees in each level can also be identified. This proposed framework provides better results when comparing to the current PEA competency model, as the criteria in this framework are systematically derived from experts rather than relying solely on the proficiency level. Although, this framework was tested with the switchgear maintenance task, the results and its systematic approach have indicated that it can also be used to develop the capability maturity model for other fields of work. Originality/value: The main originality of this research is the proposed competency analysis table, which integrates human resource development with knowledge management, risks management and management information system. Rather than performing these tasks separately for continuous quality improvement, organization can practically plan and perform the quality improvement-related tasks spontaneously. Moreover, the application of the capability maturity model to classify knowledge and skill of the maintenance tasks into maturity level is another academic value presented in this paper. The proposed framework gives the benefit to organization to classify the capability of the personnel. This is potentially beneficial to the human resource development personnel than traditional methods in the sense that it provides the information on how to develop the specific skill of the employees.